State of The Art of Corporate Entrepreneurship on State Owned Entreprises: A Bibliometrics Study - Salma Annisa; Ratih Purbasari; Margo Purnomo (Entrepreneurship Faculty, Universitas Garut, 2022)
Organizations today have been faced with a variety of dynamic environmental changes. The sustainability and sustainability of the organization can be threatened if the organization is unwilling to formulate innovations as part of a strategy to adapt. One of the determinants of the internal environment to adopt innovation is a concept called corporate entrepreneurship strategy. Corporate entrepreneurship is a fundamental element in organizational and economic development. Although many researchers have provided evidence that corporate entrepreneurship improves organizational performance, these studies only examine corporate entrepreneurship in the private sector in large companies and small and medium-sized enterprises. The development of corporate entrepreneurship research theory in state-owned enterprises is still very limited. This research will aim to provide a mapping overview of the development of corporate entrepreneurship research in state-owned enterprises that can later produce further background and deeper insights. In addition, mapping results can also be used as a basis to develop the concept of corporate entrepreneurship in state-owned enterprises. Based on the overall results of the study, it can be concluded that research on the concept of corporate entrepreneurship in state-owned enterprises in the last 26 years is really still very little done. The research findings are quite surprising because they produce indications that corporate entrepreneurship research studies on state-owned enterprises still need serious attention to be explored and exploited scientifically in today's very dynamic era of uncertainty. Organisasi saat ini telah dihadapkan dengan berbagai perubahan lingkungan yang dinamis. Keberlangsungan dan keberlanjutan organisasi dapat terancam apabila organisasi tidak mau untuk merumuskan inovasi sebagai bagian dari strategi untuk beradaptasi. Salah satu penentu lingkungan internal untuk mengadopsi inovasi adalah konsep yang disebut corporate entrepreneurship strategy. Corporate entrepreneurship merupakan elemen fundamental dalam pengembangan organisasi dan ekonomi. Meskipun banyak peneliti telah memberikan bukti bahwa corporate entrepreneurship meningkatkan kinerja organisasi, berbagai penelitian tersebut hanya meneliti corporate entrepreneurship pada sektor swasta pada perusahaan besar dan perusahaan kecil menengah. Perkembangan teori penelitian corporate entrepreneurship pada badan usaha milik negara masih sangat terbatas. Penelitian ini akan bertujuan untuk memberikan gambaran pemetaan dari perkembangan penelitian corporate entrepreneurship pada badan usaha milik negara yang nantinya dapat menghasilkan latar belakang lebih lanjut dan wawasan yang lebih mendalam. Selain itu, hasil pemetaan juga dapat digunakan sebagai dasar untuk mengembangkan konsep corporate entrepreneurship pada badan usaha milik negara. Berdasarkan hasil keseluruhan penelitian, dapat disimpulkan bahwa penelitian mengenai konsep corporate entrepreneurship pada badan usaha milik negara pada 26 tahun terakhir benar-benar masih sangat sedikit dilakukan. Temuan penelitian cukup mengejutkan karena menghasilkan indikasi bahwa kajian penelitian corporate entrepreneurship pada badan usaha milik negara masih perlu perhatian yang serius untuk dieksplorasi dan dieksploitasi secara ilmiah pada era ketidakpastian yang sangat dinamis saat ini.